If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(5+4x)=9
We move all terms to the left:
-3(5+4x)-(9)=0
We add all the numbers together, and all the variables
-3(4x+5)-9=0
We multiply parentheses
-12x-15-9=0
We add all the numbers together, and all the variables
-12x-24=0
We move all terms containing x to the left, all other terms to the right
-12x=24
x=24/-12
x=-2
| -3(-10+2x)=-24 | | 78+45p=250 | | 2z+16=2+z | | √3^x=729 | | 6x-3,6=2,4 | | 12+5x=4x-12 | | X/4-1=2+x/10= | | 2a+5=-27 | | 8=b/4+2 | | 11b+3=14b-6 | | (X+15)^2-x^2=1125 | | ½x+5=x | | 2x/7=-28 | | 2m+6=4m-12 | | 2(x=6)+x | | 2x-6=31.5 | | 5h-3=18.5 | | 12=p+5 | | x-(-6)=12+13 | | 3x=2x+10+10 | | 2x=3x+10-10 | | 2x=3x-10+10 | | 2x=3x+10+10 | | 25-5x=15 | | 71-5x=9x+13 | | 64x^{2}-96x+36=064x2−96x+36=0 | | 64x2−96x+36=0 | | 64x2−96x+36=0 | | 2a-3÷4=3a+2 | | 39c-18=33c | | 14x+-10=-10x+9 | | -10x+4=-15x+12 |